Add 3 each time
The pattern will be +2, +3, +4, +4
There are many possible answers. One is the cubic function: Un = (n3 - 9n2 + 44n - 6)/6 for n = 1, 2, 3, ...
The difference increases by one. 3, 6, 10, 15, 21, 28, 36 and so on.
3 - (-12) = 3 + 12 = 15.
The nth term, t(n) = 3*n, where n= 1, 2, 3, etc
Add 3 every time
Add 3 each time
The pattern will be +2, +3, +4, +4
multiplication pattern
There are many possible answers. One is the cubic function: Un = (n3 - 9n2 + 44n - 6)/6 for n = 1, 2, 3, ...
The difference increases by one. 3, 6, 10, 15, 21, 28, 36 and so on.
The pattern rule is: 4 5 6 7 8 and so the next number will be 33+9 = 42
Start at 1. Multiply by 3. Subtract 1. Multiply by 3. Subtract 1. Repeat this pattern.
9
3 - (-12) = 3 + 12 = 15.
It is: 3 6 12 24 48 .... double up each time